A primer on corporate governance : China - Chen, Jean Jinghan. (Corporate governance collection., 2015)
Since its opening up and economic reforms in 1979, China has undergone tremendous economic growth and social development, with a 10 percent real gross domestic product growth per year on average through 2013. In spite of such an accomplishment, the current economic growth model in China, which is mainly triggered by the export-led policy and the huge government investment, has been challenged by potential external and internal risks, which do not support sustainable economic growth in the long run. In this book, we comprehensively review the corporate governance practices in China, based on which we try to identify the major problems within such practices. We contend that these problems have been seen as the major challenges facing the Chinese economy, and we further argue that the current weakness of corporate governance practices in China can be ascribed, to a great extent, to the incompleteness and weakness of law enforcement.